2023
DOI: 10.1007/s11695-023-06485-7
|View full text |Cite|
|
Sign up to set email alerts
|

Follow-Up, Safety, and Satisfaction with Tele-bariatric Follow-Up Implemented During the COVID-19 French Lockdown: a 2-Year Follow-Up Study

Abstract: Background The COVID-19 pandemic was initially responsible for a global restricted access to healthcare resources including the follow-up of at-risk populations such as bariatric patients. We substituted face-to-face bariatric follow-up outpatient clinics (FTFC) with teleclinics (TC) during the lockdown. Material and MethodsWe retrospectively reviewed data collected on all patients scheduled for TC during the French lockdown period (March 15 to May 15, 2020) (N = 87). Our aims were to present the patients' out… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
6
0
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(7 citation statements)
references
References 40 publications
0
6
0
1
Order By: Relevance
“…The included studies were all the cross-sectional study, and each study was about telemedicine that delivered through video/audio visits. Most of included studies ( n = 32) were conducted in United States [ 17 48 ], and a few were conducted in Italy ( n = 3) [ 49 – 51 ], Spain ( n = 2) [ 52 , 53 ], Egypt ( n = 1) [ 54 ], Australia ( n = 1) [ 55 ], India ( n = 1) [ 56 ], United Kingdom ( n = 1) [ 57 ], Canada( n = 1) [ 58 ], France ( n = 1) [ 59 ], Colombia ( n = 1) [ 60 ]. The vast majority included studies ( n = 38) reported on the types of participants’ diseases, which includes head and neck otolaryngology ( n = 1) [ 17 ], pediatric ( n = 1) [ 52 ], physical, occupational, and speech therapy ( n = 1) [ 18 ], orthopaedic ( n = 1) [ 19 ], pediatric pulmonary ( n = 1) [ 20 ], cancer ( n = 4) [ 21 , 30 , 50 , 58 ], neurology ( n = 1) [ 22 ], pediatric urology ( n = 1) [ 24 ], rhinology (n = 1) [ 25 ], neuromuscular disorder ( n = 1) [ 26 ], allergy ( n = 1) [ 27 ], pediatric diabetes ( n = 1) [ 28 ], epilepsy (n = 1) [ 56 ], prechemotherapy ( n = 1) [ 29 ], pediatric rheumatology ( n = 1) [ 32 ], neurosurgery (n = 1) [ 33 ], cystic fibrosis ( n = 1) [ 35 ], pediatric and young adult type 1 diabetes ( n = 1) [ 49 ], shoulder arthroscopy ( n = 1) [ 36 ], pediatric surgery ( n = 1) [ 53 ], vascular surgery ( n = 1) [ 57 ], maternal mental health and substance use disorder treatment ( n = 1) [ 38 ], referral ( n = 1) [ 39 ], dermatology ( n = 1) [ 40 ], endovascular neurosurgery ( n = 1) [ ...…”
Section: Resultsmentioning
confidence: 99%
See 4 more Smart Citations
“…The included studies were all the cross-sectional study, and each study was about telemedicine that delivered through video/audio visits. Most of included studies ( n = 32) were conducted in United States [ 17 48 ], and a few were conducted in Italy ( n = 3) [ 49 – 51 ], Spain ( n = 2) [ 52 , 53 ], Egypt ( n = 1) [ 54 ], Australia ( n = 1) [ 55 ], India ( n = 1) [ 56 ], United Kingdom ( n = 1) [ 57 ], Canada( n = 1) [ 58 ], France ( n = 1) [ 59 ], Colombia ( n = 1) [ 60 ]. The vast majority included studies ( n = 38) reported on the types of participants’ diseases, which includes head and neck otolaryngology ( n = 1) [ 17 ], pediatric ( n = 1) [ 52 ], physical, occupational, and speech therapy ( n = 1) [ 18 ], orthopaedic ( n = 1) [ 19 ], pediatric pulmonary ( n = 1) [ 20 ], cancer ( n = 4) [ 21 , 30 , 50 , 58 ], neurology ( n = 1) [ 22 ], pediatric urology ( n = 1) [ 24 ], rhinology (n = 1) [ 25 ], neuromuscular disorder ( n = 1) [ 26 ], allergy ( n = 1) [ 27 ], pediatric diabetes ( n = 1) [ 28 ], epilepsy (n = 1) [ 56 ], prechemotherapy ( n = 1) [ 29 ], pediatric rheumatology ( n = 1) [ 32 ], neurosurgery (n = 1) [ 33 ], cystic fibrosis ( n = 1) [ 35 ], pediatric and young adult type 1 diabetes ( n = 1) [ 49 ], shoulder arthroscopy ( n = 1) [ 36 ], pediatric surgery ( n = 1) [ 53 ], vascular surgery ( n = 1) [ 57 ], maternal mental health and substance use disorder treatment ( n = 1) [ 38 ], referral ( n = 1) [ 39 ], dermatology ( n = 1) [ 40 ], endovascular neurosurgery ( n = 1) [ ...…”
Section: Resultsmentioning
confidence: 99%
“…While the remaining studies ( n = 6) did not limit the patient types [ 23 , 31 , 34 , 37 , 54 , 55 ]. For the evaluation questionnaire, there are part of studies ( n = 16) using existing questionnaires [ 17 , 22 , 26 , 28 , 30 , 32 34 , 42 , 46 , 47 , 50 , 55 , 56 , 58 , 59 ], a few of studies’ questionnaire ( n = 3) were designed based on different studies [ 21 , 24 , 49 ], several studies ( n = 7) evaluating by self-developed questionnaires [ 19 , 25 , 29 , 39 , 51 , 57 , 60 ], and some ( n = 18) studies did not mension the specific questionnaires used [ 18 , 20 , 23 , 27 , 31 , 35 38 , 40 , 41 , 43 45 , 48 , 52 54 ]. In addition, the questionnaires used in several studies ( n = 18) were divided into various dimensions [ 17 , 20 , 23 , 24 , 26 , 32 , 34 , 37 , 38 , 44 , 47 , 49 – 51 , 53 55 , 57 ].…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations